Stand by your man: Wives' emotion work during men's unemployment - RAO, Aliya Hamid (Institutional Knowledge at Singapore Management University, 2017)
Recent research on unemployment has not sufficiently acknowledged how unemployment reverberates within families, particularly emotionally. This article uses data from more than 50 in‐depth interviews to illuminate the emotional demands that men's unemployment makes beyond the unemployed individual. It shows that wives of unemployed men do two types of emotion work—self‐focused and other‐focused—and both are aimed toward facilitating husbands' success in the emotionally arduous white‐collar job‐search process. This article extends research on emotion work by suggesting that participants perceive wives' emotion work as a resource with potential economic benefits in the form of unemployed men's reemployment. The findings furthermore suggest that as a resource, wives' emotion work is shaped by the demands of the labor market that their husbands encounter.